Seroprevalence survey for Varicella among healthcare workers and medical students in Italy - Ottavia Balbi; Savino Baldi; Stefano Rizza; Antonio Pietroiusti; Stefano Perrone; Luca Coppeta (Taylor & Francis Group, 2021)
Varicella is a potentially serious infectious disease caused by Varicella-Zoster Virus (VZV). In Italy childhood varicella vaccine have gradually introduced into national immunization program since 2003 and from 2017 a two-doses schedule has been stated nationally for all newborns and has become compulsory for school attendance. VZV exposures among healthcare workers (HCWs) and patients can be really dangerous and expensive. According to Centers of Disease Control and Italian national immunization plan health care, institutions should verify that all HCWs have clear evidence of immunity to VZV and should ensure that susceptible subjects will receive 2 doses of VZV vaccine. Currently, the vaccination of HCWs is not compulsory in Italy and the risk of varicella infection among these subjects is not well known. We evaluated the clinical records of 840 HCWs (256 male and 584 female) who underwent the annual occupational screening, from 1st January to 31st August 2018. HCWs were divided into three subgroups according to their age: 18-30, 31-40, and over 40 years old. We compared the mean values of IgG-specific antibodies between the age group through analysis of variance (ANOVA). A total of 784 (93.33%) HCWs were protected for VZV IgG antibodies level. There wasn't a significant difference between male and female while was found between age group (P < 0.001). Protection levels for varicella are inadequate among HCWs. Despite the epidemiology of varicella in general population has changed with the implementation of the childhood varicella vaccination program transmission of VZV in hospitals is still a serious problem, so it is necessary to increase prevention activities in these settings, including vaccination.